2006
DOI: 10.1007/s11258-005-9048-5
|View full text |Cite
|
Sign up to set email alerts
|

Alpine vascular plant species richness: the importance of daily maximum temperature and pH

Abstract: Species richness in the alpine zone varies dramatically when communities are compared. We explored (i) which stress and disturbance factors were highly correlated with species richness, (ii) whether the intermediate stress hypothesis (ISH) and the intermediate disturbance hypothesis (IDH) can be applied to alpine ecosystems, and (iii) whether standing crop can be used as an easily measurable surrogate for causal factors determining species richness in the alpine zone. Species numbers and standing crop were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 37 publications
7
23
0
Order By: Relevance
“…They showed that, besides soil pH, length of growing season and daily maximum temperature (measured 15 cm above ground) were important abiotic factors discerning snowbed communities from other alpine plant communities. Furthermore, the study of Vonlanthen et al (2006b) as well as our study found that T max and T mean were highly correlated and that both significantly influenced floristic composition while T min was of lower relevance in this regard. Our results, therefore, suggest that growing season length and T max are not only relevant explanatory variables to discriminate among the alpine plant communities (Vonlanthen et al 2006a), but also for small-scale vegetation patterns within alpine snowbed communities.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…They showed that, besides soil pH, length of growing season and daily maximum temperature (measured 15 cm above ground) were important abiotic factors discerning snowbed communities from other alpine plant communities. Furthermore, the study of Vonlanthen et al (2006b) as well as our study found that T max and T mean were highly correlated and that both significantly influenced floristic composition while T min was of lower relevance in this regard. Our results, therefore, suggest that growing season length and T max are not only relevant explanatory variables to discriminate among the alpine plant communities (Vonlanthen et al 2006a), but also for small-scale vegetation patterns within alpine snowbed communities.…”
Section: Discussionsupporting
confidence: 67%
“…Short growing seasons and low temperature are well known alpine stress factors (e.g. Komárková 1993;Kammer and Möhl 2002;Vonlanthen et al 2006b) delimiting the number of species able to grow under these conditions. Only well adapted plant species could grow and reproduce at the harsher end of the environmental gradients under study.…”
Section: Discussionmentioning
confidence: 99%
“…Plant size of all species occurring in snowbeds was consistently low (mean canopy height approximately 5 cm). Peak standing biomass was 14.5 g m −2 with a vegetation cover of 85% (Vonlanthen et al 2006b).…”
Section: Methodsmentioning
confidence: 99%
“…), and data on the effect of environmental gradients on the patterns of distribution of plant communities in alpine ranges are in general very rare (Vonlanthen et al. ).…”
Section: Introductionmentioning
confidence: 99%